The evaluation of the research on the bioethanol: A scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the literature on the bioethanol published during the last three decades based on the Science Citation Index Expanded (SCIE) and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this study reveal that the research output on the bioethanol and the citations received have grown exponentially during this period especially after 2004 with paralleling enormous changes in the research landscape. The US, China, and Japan have been the three most prolific countries. The "Tech Univ Denmark" has been the most prolific institution and "Zacchi G" of Sweden has been the most prolific author. "Bioresource Technology" has been the most prolific journal whilst "Biotechnology & Applied Microbiology" has been the most prolific subject area. "H-index" was 61 and "Demirbas A" [1] has had the highest impact on the literature. The scientometric analysis has a great potential to gain valuable insights into the evolution of the research on the bioethanol, complementing the scientometric studies in the other fields of the renewable energies such as biohydrogen, biodiesel, bioenergy, biofuels, and microbial fuel cells, providing a unique insight on the incentive structures for all the key stakeholders in the field.
Keywords: Bioethanol; Renewable fuels; Research evaluation; Scientometrics; Web of Knowledge